Mitigasi Risiko Keselamatan Dan Kesehatan Kerja (K3) - Purwanto, Adi; Handayani, Dwi Iryaning; Hardiyo, Joko (Students Journal of Engineering, 2015)
Risk management of occupational safety and health risk in the industrial world especially in PT.KutaiTimber Indonesia paticle board factory that encourages safety and healty efforts way of mitigasing all therisk that exist. The method used in this researh is the management of risk by Australian/New Zealand RiskManagement Standart AS/NZS 4360:2004. The first stage in this risk manajement is to identify the risk byusing a fishbone diagram. The second stage is to do the risk assessment analysis of the consequences andlikelihood. From the results of the risk analysis found 2 exstreme risk levels, 7 high risk levels and 4 lowrisk levels. Exstreme risk level and high risk level is classified as the most serious risk that could result indeath so that in can be done first priority handling. Exstreme risk events worker falls while walking acrossthe top of the stairs in forming and hot press. Mitigation measures is to give warning sign safety forbiddenjoked as the worker walked across the stairs, put a wooden board as the base that is not slippery stairs,iron fences plus higher as a safety handrails and worker are required equipment safety shoes that fitunderneath is still thick with the standart.Keyword : Mitigation measure, risk management AS/NZS 4360:2004, risk identify and risk assessment